Doped holographic superconductor in an external magnetic field - Correa, Diego Hernán (2019)
We add the magnetic field axis to the holographic model for a doped superconductor proposed by Kiritsis and Li. We explore the resulting superconducting dome, in a particular region of parameters in which the equations for the superconductor can be mapped into the previously known undoped case.